Unclogging the heart: the potential of statins to reverse coronary artery blockage - Oza, Yugam; Pathak, Kesha; Rana, Rimsha; Mehta, Diya; Patel, Krina (International Journal of Research in Medical Sciences, 2025)
Acute coronary syndrome (ACS) comprises three life-threatening cardiovascular conditions-unstable angina, non-ST elevation myocardial infarction (NSTEMI), and ST elevation myocardial infarction (STEMI)-all characterized by reduced myocardial blood flow leading to ischemia and potential cardiac tissue damage. Established risk factors for ACS include age over 50, smoking, obesity, diabetes mellitus, and hypertension. Statins, a cornerstone in cardiovascular disease management, function by inhibiting HMG-CoA reductase, a key enzyme in hepatic cholesterol synthesis. Beyond lipid-lowering, emerging evidence supports their role in stabilizing and regressing atherosclerotic plaques. This narrative review explores the impact of statin therapy on arterial blockages associated with ACS. Data from multiple clinical trials and studies indicate that statins significantly reduce both morbidity and mortality in ACS patients. Notably, intensive statin regimens, particularly with rosuvastatin, have demonstrated greater efficacy in inducing plaque regression and improving plaque stability compared to standard therapy. In summary, statins are integral to the acute and long-term management of ACS, offering both anti-inflammatory and plaque-stabilizing effects. Their ability to reverse atherosclerosis, especially with high-intensity therapy, underscores their essential role in reducing adverse cardiovascular outcomes. The robust evidence supporting their use highlights the necessity of early initiation and sustained administration in ACS patients to improve prognosis and survival.